The influence of helix morphology on co-operative polyamide backbone conformational flexibility in peptide nucleic acid complexes - Topham, Christopher M.; Smith, Jeremy C. (Journal of molecular biology, 1999)
A systematic analysis of peptide nucleic acid (PNA) complexes deposited in the Protein Data Bank has been carried out using a set of contiguous atom torsion angle definitions. The analysis is complemented by molecular mechanics adiabatic potential energy calculations on hybrid PNA-nucleic acid model systems. Hitherto unobserved correlations in the values of the (α and ϵ) dihedral angles flanking the backbone secondary amide bond are found. This dihedral coupling forms the basis of a PNA backbone conformation classification scheme. Six conformations are thus characterised in experimental structures. Helix morphology is found to exert a significant influence on backbone conformation and flexibility: Watson-Crick PNA strands in complexes with DNA and RNA, that possess A-like base-pair stacking, adopt backbone conformations distinct from those in PNA·DNA-PNA triplex and PNA-PNA duplex P-helix forms. Solvation effects on Watson-Crick PNA backbone conformation in heterotriplexes are discussed and the possible involvement of inter-conformational transitions and dihedral angle uncoupling in asymmetric heteroduplex base-pair breathing is suggested.